Constipation preceding Parkinson's disease: a systematic review and meta-analysis. Issue 7 (7th September 2015) - Adams-Carr, Kerala L; Bestwick, Jonathan P; Shribman, Samuel; Lees, Andrew; Schrag, Anette; Noyce, Alastair J
Abstract : Objective: To systematically review published literature to estimate the magnitude of association between premorbid constipation and later diagnosis of Parkinson's disease. Background: Constipation is a recognised non-motor feature of Parkinson's and has been reported to predate diagnosis in a number of observational studies. Methods: A systematic review and meta-analysis was carried out following the Meta-analysis Of Observational Studies in Epidemiology (MOOSE) criteria. A literature search was undertaken in December 2014 using PubMed and the search terms 'Parkinson's disease' and 'constipation'. Articles were screened for suitability and reviewed against inclusion and exclusion criteria. Studies were included if they assessed constipation by means of a structured questionnaire or if constipation/drugs used to treat constipation were coded in patient medical records. Data were extracted using a standardised template and effect size estimates combined using a fixed-effects model. Heterogeneity was explored with the I 2 statistic. Results: 9 studies were included in the meta-analysis, with a combined sample size of 741 593 participants. Those with constipation had a pooled OR of 2.27 (95% CI 2.09 to 2.46) for developing subsequent Parkinson's disease compared with those without constipation. Weak evidence for heterogeneity was found (I 2 =18.9%, p=0.282). Restricting analysis to studies assessing constipation more than 10 years prior to Parkinson's disease gave a pooled OR of 2.13 (95% CI 1.78 to 2.56; I 2 =0.0%). Conclusions: This systematic review and meta-analysis demonstrates that people with constipation are at a higher risk of developing Parkinson's disease compared with those without and that constipation can predate Parkinson's diagnosis by over a decade.